PEMBINAAN GIZI SEIMBANG BALITA MELALUI KEGIATAN KELAS IBU BALITA DI POSYANDU KELURAHAN POLEWALI - Sriwidyastuti Sriwidyastuti; Susilawati Susilawati; Ermawati Ermawati; Sumarni Sumarni; Musdalifah Musdalifah (Yayasan Nusantara Hasana Berdikari, 2026)
Currently, toddlers are among the age group vulnerable to nutritional problems due to malnutrition. Nutritional problems in toddlers can cause short-term and long-term effects on child development, such as impaired brain development, physical growth retardation, decreased immunity, metabolic disorders, and an increased risk of non-communicable diseases. Stunting, wasting, and underweight are related to nutritional status in children. The purpose of this activity is to increase the knowledge of toddler mothers regarding balanced nutrition. The method of community service is balanced nutrition counseling in toddler mother class activities using PowerPoint and banner media. Before the presentation of the material, participants first took a pre-test on balanced nutrition and continued with material delivery and evaluation through a post-test. The results of community service activities through counseling showed an increase in knowledge of toddler mothers about balanced nutrition. This community service activity was carried out as an effort to increase mothers' awareness in providing a nutritious menu for the growth and development of toddlers.